Dosimetric Properties of the Newly Developed LiF:Mg,Cu,Si TL Material (Journal of Scientific Research, 2012)
The dosimetric properties of the newly developed thermoluminescence (TL) material (LiF:Mg,Cu,Si) at Korea Atomic Energy Research Institute (KAERI) were investigated. The energy response of the detector was performed for photon energies from 20 to 662 keV. The dose response for this TL material (LiF:Mg,Cu,Si) was linear up to 10 Gy and a sub-linear response was observed for higher doses. The reusability of this newly developed TL detector sufficiently satisfied IEC standards. Detection threshold of LiF:Mg,Cu,Si TL material was investigated and found to be 930 nGy by Harshaw 4500 TLD reader. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi: http://dx.doi.org/10.3329/jsr.v5i1.11935        J. Sci. Res. 5 (1), 25-31  (2013)